ANALISIS MINAT DAN HASIL BELAJAR SISWA PADA MATERI PENGUKURAN KELAS X SMAN UMBULSARI - Hayuningtyas, Sekargupita; Anggraeni, Firdha Kusuma Ayu; Supriadi, Bambang (Universitas Jember, 2024)
The research conducted at SMAN Umbulsari aimed to analyze the relationship between students' interest in physics learning and their learning outcomes. The study employed quantitative research methods and included all class X.2 students, totaling 35 individuals. The majority of students exhibited a good level of interest in learning physics, with 86% reporting feelings of happiness regarding their studies. Additionally, 12 students achieved high learning outcomes. The analysis revealed a significant positive correlation (correlation coefficient of 0.366 with a significance level of 0.031) between students' interest in learning physics and their learning outcomes. This suggests that higher levels of interest in learning correlate with better academic performance. In conclusion, the research indicates that students who are more interested in learning physics tend to achieve better learning outcomes compared to those with lower levels of interest